PERSPECTIVES ON NON-VIOLENCE IN THE MOKSA-DHARMA-PARVAN OF THE MAHABHARATA: . - Sutton, Nicholas (Journal of Dharma, 2002)
It might seem that the Mahabharata will have little to offer by way of teachings on the subject of non-violence. It is after all primarily an epic tale of conflict, quarrel, war and triumph, with several lengthy passages devoted to descriptions of battle and the prowess and heroism of its principal protagonists. Furthermore, the best known of all the Mahabharata's passages of religious instruction is the Bhagavad-gita, which has as its initial premise the assertion that a warrior must wage war, both as an act of religious duty and as a form of Yoga that can lead to salvation. Hence Krsna demands of Arjuna at the very beginning of his exposition, tasmad yudhyasva bharata, 'Therefore, Bharata, you should wage war.' (2.18)